Gap Junction in the Teleost Fish Lineage: Duplicated Connexins May Contribute to Skin Pattern Formation and Body Shape Determination - Watanabe, Masakatsu (Frontiers in Cell and Developmental Biology, 2017)
Gap junctions are intercellular channels that allow passage of ions and small molecules between adjacent cells. Gap junctions in vertebrates are composed of connexons, which are an assembly of six proteins, connexins. Docking of two connexons on the opposite cell surfaces forms a gap junction between the cytoplasm of two neighboring cells. Connexins compose a family of structurally related four-pass transmembrane proteins. In mammals, there are approximately 20 connexins, each of which contributes to unique permeability of gap junctions, and mutations of some connexin-encoding genes are associated with human diseases. Zebrafish has been predicted to contain 39 connexin-encoding genes; the high number can be attributed to gene duplication during fish evolution, which resulted in diversified functions of gap junctions in teleosts. The determination of body shapes and skin patterns in animal species is an intriguing question. Mathematical models suggest principle mechanisms explaining the diversification of animal morphology. Recent studies have revealed the involvement of gap junctions in fish morphological diversity, including skin pattern formation and body shape determination. This review focuses on connexins in teleosts, which are integrated in the mathematical models explaining morphological diversity of animal skin patterns and body shapes.